Fios e furos: a trama da subjetividade e a educação - Souza, Mériti De [UNESP] (ANPEd - Associação Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
Discusses the constitution of subjectivity cut through with pathos and logos and addressed to the singular and the collective. This conception requires the analysis of that which is excluded from the individualised identity of modern man and of knowledge as anchored exclusively in reason. Based on research developed with the school population and on listening to speeches produced by these people situated in subjective places with relation to knowledge, we question the possibility of pedagogical practice constituting experience, which produces subjective effects.

Discute a constituição da subjetividade atravessada pelo pathos e pelo logos e remetida ao singular e ao coletivo. Essa concepção demanda a análise do excluído da identidade individualizada do homem moderno e do conhecimento como ancorado exclusivamente na razão. Considerando o trabalho desenvolvido com a população escolar e a escuta dos discursos produzidos pela alocação dessas pessoas em lugares subjetivos perante o saber, indaga-se a possibilidade da prática pedagógica constituir-se em experiência produzindo efeitos de subjetivação.
Threads and holes: the plot of subjectivity and education
Keywords: subjectivity; education; school; modernity; subjetividade; educação; escola; modernidade